Bioproduction of D‐allulose: Properties, applications, purification, and future perspectives. Issue 6 (19th October 2021) - Hu, Mengying; Li, Mengli; Jiang, Bo; Zhang, Tao
Abstract: D‐allulose is the C‐3 epimer of D‐fructose, which rarely exists in nature, and can be biosynthesized from D‐fructose by the catalysis of D‐psicose 3‐epimerase. D‐allulose is safe for human consumption and was recently approved by the United States Food and Drug Administration for food applications. It is not only able be used in food and dietary supplements as a low‐calorie sweetener, but also modulates a variety of physiological functions. D‐allulose has gained increasing attention owing to its excellent properties. This article presents a review of recent progress on the properties, applications, and bioproduction progress of D‐allulose.